'A plus for our students': the construction of Mandarin Chinese as an elite language in an international school in Barcelona. Issue 5 (28th May 2019) - Codó, Eva; Sunyol, Andrea
ABSTRACT: Mandarin Chinese is the fastest growing foreign language by number of students in the world [Ding and Saunders 2006. "Talking up China: An Analysis of China's Rising Cultural Power and Global Promotion of the Chinese Language." East Asia 23 (2): 3–33], but little is known about how it is taking hold in compulsory education in different countries. This paper examines the institutionalisation of Mandarin in an elite school located near Barcelona, Spain, which, due to stagnant enrolment rates, was rebranded as 'international' in 2008. Data on the evolution and shifting legitimation of the Chinese programme was gathered through a two-year critical sociolinguistic ethnography. It included observations, visual materials, institutional discourses, questionnaire data and in-depth interviews with key social actors. The results show that Chinese has been highly instrumental for the process of re-elitisation of the school through multilingualisation (and internationalisation), because it allows institutional agents to mobilise both the discourse of cognitive/attitudinal benefits and forms of linguistic capitalisation avant-la-lettre . Yet, among most families and students, there is sharp awareness of the speculative nature of Chinese as capital whose returns in the present can only be guaranteed in the logic of accumulation and as providing an index of students' embodiment of neoliberal subjectivities. For the school, Chinese symbolises its zeal to constantly search for new sources of (potential) distinction and academic excellence.